Abu Sayaf’s New Leader: Yasser Igasan the Religious Scholar - Taharudin Piang Ampatuan (2016)
THE COMMANDING General of the Philippine Army, LtGen. Romeo Tolentino announced recently that the radical Abu Sayaf Group (ASG) had chosen a new leader in the person of the militant Middle East-trained religious scholar, Ustaz Yasser Igasan. Although Tolentino discounted the capability of Igasan to lead the group, it is interesting to note that the new leader possesses the traits which security experts have long argued ASG has been lacking — a religious anchor and an ideological compass. With Igasan’s emergence, the ASG seems to have finally plugged this gap as the new leader is both an Islamic scholar and a recognized ideologue.